Peningkatan Pelafalan Bunyi pada Percakapan Bahasa Inggris Peserta Didik Kelas Xi SMA Budi Utama Melalui Metode Audiolingual - Kalpikayanti, Ni Luh Putu (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2017)
This journal is aimed to analyse the ability of the eleventh students of SMA Budi Utama to pronounce the dialog before and after using audiolingual method and alsoanalizing the factors of mistake of pronounce the dialog. The data were collected by observing, recording the student pronunciations,anddoing direct interview to the English teachers related to the aims of the study.Quantitative method was used to analyse the numeric data based on the rubric and qualitative method was used to analyse the fonetic.   The result of the analysis show that before using Audiolingual method students difficult to pronounce sounds[ð],[?], [ð], [?], [?], diphthong sounds[a?], [e?], [a?], and words ending by - nd and – ght. Students are tend to change the foreign sound with their own articulation such as sound [ð] changed by sound[d], sound[ ? ] changed by sound [t], sound [ ? ] changed by sound [s], sound [ ? ] changed by sound [s]. One example word which showed the changes of mistaken percentage is [ thought ]from 100% decrease becomes 56% and more decrease in second cycles becomes 12%. Mistakes of pronounce of the students are caused by the influence of their mother tongue and their first language, the lack of teaching method, media, and supporting facilities from the school, students motivation, and their learn interest still less are caused by limited of the supporting facilities of the school